ANALISIS PENGARUH CITRA MEREK, KESADARAN MEREK DAN PERSEPSI KUALITAS TERHADAP KEPUTUSAN PEMBELIAN DENGAN LOYALITAS MEREK SEBAGAI VARIABEL INTERVENING (Studi pada Konsumen Cokelat Delfi di Universitas Diponegoro) - Prahasti, Seilla Anjani Maya; Rahardjo, Susilo Toto (Faculty of Economics and Business Diponegoro University, 2018)
This research is motivated by the tight competition of chocolate confectionery brand in Indonesia. It impact the brand performance of an Delfi in the last three years. This study aimed to analyze the effect of brand image, brand awareness and perceived quality to consumer purchase decision through brand loyalty as the intervening variable. This research was conducted on Chocolate Delfi consumer at Diponegoro University Semarang.The sampling method used in this research is non-probability sampling with purposive sampling technique. Samples were collected from 100 respondents with the criteria of students Diponegoro University and who had ever done purchase transaction of Chocolate Delfi more than two times. The analysis method used in this study is quantitative method including validity and reliability test, classic assumption test, multiple regression analysis, t test, F test, coefficient determination using SPSS and sobel test.The result of this research showed that brand image, brand awareness and perceived quality has positive and significant effect on cunsumer purchase decision. Brand loyalty has positive and significant effect on consumer purchase decision. The result of sobel test showed that brand image, brand awareness and perceived quality have indirect effect on consumer purchase decision through brand loyalty.